Exploring the Efficacy of Workshops as a Professional Teacher Development Strategy for Inclusive Education in South African Schools: Teachers' Perspectives - Simon Mfula Ndlovu; Mahlapahlapana Johannes Themane; Baby Inneth Makofane; Hunadi Mphahlele (Noyam Journals, 2024)
For inclusive education to be a success, in-service teachers need to be thoroughly trained. learning and professional development programmes have been initiated across the globe including South Africa to prepare teachers. Workshops are well-known training methods in inclusive education. Surprisingly, despite their existence, literature points out that there's still an inadequacy of teacher training. This complaint makes one question the efficacy of the workshops. To this end, this study explored the efficacy of workshops on Inclusive Education (IE) for Foundation Phase (FP) teachers in the Capricorn District of Limpopo Province. To achieve this, the case-study design in qualitative research was used. A purposive sampling strategy was used to sample 11 FP teachers from three ordinary schools. Data was collected through document reviews, in-depth interviews, and a focus group interview. The data was analysed through the thematic analysis method. The analysis revealed that according to teachers the workshops are not effective, for the following reasons: (i) the workshops only provide a theory that does not match the reality of the schools; (ii) the workshops are too short and not sufficiently informative; (iii) through teacher agency, teachers improvise to achieve IE. These findings suggest that IE workshops do get implemented in South African schools, however, their efficacy is questionable. Therefore, a proper model for the workshops that will be considerate of the schools' context should be devised. This study may inform policy makers workshop facilitators, and researchers about what is working and what is not working regarding inclusion workshops.